Acceptance and continued use of digital libraries by postgraduate students in Malaysian Intensive Research Universities / Abd Latif Abdul Rahman - Abdul Rahman, Abd Latif (Institute of Graduate Studies, UiTM, 2012)
The digital library is regarded as a new information system product in libraries and information centres around the world. It is also regarded as one of the most innovative efforts taken by library and information professionals in their attempt to enhance the library and information services for their users. Library and information professionals are capitalizing on the flexibility and advantages of the digital library to offer new and sophisticated services to their library users. Currently, users are already relying on the availability of digital libraries for their information needs to support their daily tasks. In the context of the university environment, the digital library in the university is being utilized by students and academics almost constantly. In this context, librarians and information professionals who are responsible for the development of a digital library need to understand the intricacies of it so that the advantages and benefits can be exploited to better provide library and information services. One of the most important aspects of the digital library in the university environment is its acceptance and continued use by the university community, particularly by students.